2004
DOI: 10.1002/ijc.20768
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear or cytoplasmic expression of survivin: What is the significance?

Abstract: Growing evidence suggests that survivin expression in cancer cell nuclei may represent an important prognostic marker to predict disease outcome for cancer patients. Current reports in this research area, however, are inconsistent and propose opposing conclusions regarding the significance and prognostic value of survivin nuclear expression. The aim of our study is to review and discuss the data reported in the original publications. We have also provided new experimental data to support our view regarding the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
198
4
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(224 citation statements)
references
References 30 publications
20
198
4
2
Order By: Relevance
“…These results may in part correspond to the pivotal study of survivin in DLBCL by Adida et co-workers, who demonstrated an adverse role of cytoplasmic survivin on 222 patients [10]. Other reasons that may influence results are different clones of antisurvivin antibody used and differences in tumor tissue processing [5]. In contrast to all previous studies of survivin in DLBCL, our patients were treated with rituximab and CHOP.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…These results may in part correspond to the pivotal study of survivin in DLBCL by Adida et co-workers, who demonstrated an adverse role of cytoplasmic survivin on 222 patients [10]. Other reasons that may influence results are different clones of antisurvivin antibody used and differences in tumor tissue processing [5]. In contrast to all previous studies of survivin in DLBCL, our patients were treated with rituximab and CHOP.…”
Section: Discussionsupporting
confidence: 72%
“…Although IAPs were originally described as caspase inhibitors, more recent studies identified survivin as a regulator of mitosis, a broad cytoprotective factor, and an effector of cellular adaptation to stress [4]. Survivin expression was detected in various tumors and mostly correlated with inferior outcome [5]. Immunohistochemical expression of survivin was also investigated in DLBCL [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…49,50 It has been proposed that variations in immunostaining and interpretation might be among the contributing factors to these conflicting results. 51 The distinct nuclear and cytoplasmic staining in our study is unequivocal, and we provided detailed quantitative data on the nuclear staining than Survivin nuclear index in urothelial carcinoma W Yin et al previous reports. Our data clearly showed that BIRC5 nuclear labeling index, but not cytoplasmic staining, was significantly associated with tumor grade, stage, and poorer prognosis for Ta/T1 urothelial carcinomas.…”
Section: Discussionsupporting
confidence: 64%
“…Different prognostic significance of BIRC5 nuclear labeling in several tumor types has been reported in recent years, [45][46][47][48][49][50] as summarized in reference Li et al 51 For example, correlation of BIRC5 nuclear (but not cytoplasmic) staining with poor prognosis has been reported in ependymoma, esophageal squamous cell carcinoma, hepatocellular carcinoma, mantel cell lymphoma, and non-small cell lung cancer. [45][46][47][48] Paradoxically, BIRC5 nuclear staining was reported to be associated with better prognosis in gastric cancer and breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of detection of cytoplasmic to nuclear reactivity can vary depending on the antibodies used (Fortugno et al, 2001). A recent review of the significance of survivin in cancers generally (Li et al, 2005) identified more studies in which it was found to relate to poorer prognosis, and recommended that for technical reasons nuclear and cytoplasmic staining should not be considered separately, the approach used in the present study.…”
Section: Discussionmentioning
confidence: 99%